ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2010 - 2013 - Nedi Hendri (Universitas Muhammadiyah Metro, 2015)
This research conducted in the field of agriculture and mining companies listed on the Indonesia Stock Exchange. The purpose of this research is to examine the impact firm size, firm public accounting size, consistency become a client, operation of complexity, profit of loss of business and auditor opinion toward audit delay. Sampling method that used is purposive sampling and the result are 21 firms as sample. This research is done for 2010 – 2013 period. Data that used in this research is financial statements from each company, publized through website www.idx.co.id. The data which have already collected are processed with statistic deskriptif test, classic assumption test before hypothesis test. Software SPSS 17 for windows is used to test in this research. The result of this research shows that independent variables simultaneously influenced 12,3 percent of dependent variable. Partially, consistency become a client have negative significant toward audit delay. The other variables such as firm size, firm public accounting size, operation of complexity, profit or loss of business and auditor opinion do not affecting audit delay. Key words : audit delay, firm size, firm public accounting size, consistency become a client, operation of complexity, profit or loss of business and auditor opinion.